Maqashid Asy-Syariah sebagai Kerangka Analisis Reformasi Kebijakan Perpajakan Nasional Indonesia - Sulma Nabilah; Fuad Yanuar Akhmad Rifai; Qurotul Aini (ARBITRASE: Journal of Economics and Accounting, 2026)
This study examines the integration of Maq??id al-syar?‘ah  within Indonesia’s national taxation system as a framework for evaluating fiscal justice and public welfare. Previous studies generally discuss taxation from the perspectives of public finance, tax administration, or normative Islamic law. In contrast, this study positions Maq??id al-syar?‘ah  as an analytical framework for assessing the ethical orientation and social legitimacy of contemporary fiscal policy. This research employs a qualitative approach using library research. Data were obtained from classical and contemporary literature on Maq??id al-syar?‘ah , Islamic economics, taxation studies, and Indonesian fiscal policy documents, including tax regulations and state budget policies (APBN). Data analysis was conducted using qualitative content analysis to identify the relationship between taxation policies and the five essential objectives of Maq??id al-syar?‘ah  (al-dar?riyy?t al-khamsah), namely the protection of religion, life, intellect, lineage, and wealth. The findings reveal that Indonesia’s taxation system substantively reflects several maq??id dimensions, particularly through redistributive fiscal policies such as progressive taxation, public expenditure on education and healthcare, and social welfare programs. However, the integration of maq??id values in fiscal policy remains largely implicit and has not yet been systematically incorporated into the conceptual foundation of taxation regulations. This condition indicates that fiscal policy is still predominantly oriented toward revenue optimization and administrative efficiency rather than distributive justice and social welfare. This study contributes a conceptual perspective by positioning Maq??id al-syar?‘ah  not merely as a normative Islamic doctrine, but as a critical analytical framework for evaluating modern taxation systems. The study also offers an alternative approach for developing fiscal policies that are more equitable, welfare-oriented, ethically legitimate, and socially accountable.